Sistem Penataan Arsip Dinamis Inaktif di Badan Kepegawaian Daerah Kabupaten Padang Pariaman - Agustia, Sylvina Dwi; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were (1) describe the arrangement of the system of inactive records used in the Regional Employment Board of Padang Pariaman district, and (2) describe the constraints faced when structuring inactive records in the Regional Employment Board of Padang Pariaman district. with the theory discussed, conclusions, and reporting. The results of this study were as follows: (1) the system records the arrangement inactive in District Employment Agency in Padang Pariaman still jumbled arrangement and structuring procedure is less effective that its archives are still frequent difficulties in the retrieval process. Systems should be applied in accordance with the arrangement of archival science and providing training for existing archivists; (2) the constraints faced by the frequent occurrence of accumulation of inactive records in the Regional Employment Board of Padang Pariaman District, and the lack of awareness about the importance of the archive. Meanwhile, the lack of attention from the technical implementation will make the situation more chaotic because the archive files are not managed in accordance with procedures. Has not been running properly so finding constraints in retrieval. Keywords: records; inactive records